(untitled) (Journal of Engineering, 2013)
This research is devoted to study the strengthening technique for the existing reinforced concrete beams using external post-tensioning. An analytical methodology is proposed to predict the value of the effective prestress force for the external tendons required to close cracks in existing beams. The external prestressing force required to close cracks in existing members is only a part from the total strengthening force. A computer program created by Oukaili (1997) and developed by Alhawwassi (2008) to evaluate curvature and deflection for reinforced concrete beams or internally prestressed concrete beams is modified to evaluate the deflection and the stress of the external tendons for the externally strengthened beams using Matlab 7.0. The analytical investigation is implemented on three ideal reinforced concrete beam models, each model is considered to be strengthened using three types of external tendon profile (straight, draped and double draped), where each type of tendon profile is analyzed separately. No comparisons were made with analytical or experimental investigations, because no publications for this kind of studies were found.